Technology and the Dream Reflections on the Black Experience at MIT, 1941-1999 - Williams, Clarence G. (The MIT Press, 2003)
Transcripts of more than seventy-five oral history interviews in which the interviewees assess their MIT experience and reflect on the role of blacks at MIT and beyond. This book grew out of the Blacks at MIT History Project, whose mission is to document the black presence at MIT. The main body of the text consists of transcripts of more than seventy-five oral history interviews, in which the interviewees assess their MIT experience and reflect on the role of blacks at MIT and beyond. Although most of the interviewees are present or former students, black faculty, administrators, and staff are also represented, as are nonblack faculty and administrators who have had an impact on blacks at MIT. The interviewees were selected with an eye to presenting the broadest range of issues and personalities, as well as a representative cross section by time period and category. Each interviewee was asked to discuss family background; education; role models and mentors; experiences of racism and race-related issues; choice of field and career; goals; adjustment to the MIT environment; best and worst MIT experiences; experience with MIT support services; relationships with MIT students, faculty, and staff; advice to present or potential MIT students; and advice to the MIT administration. A recurrent theme is that MIT's rigorous teaching instills the confidence to deal with just about any hurdle in professional life, and that an MIT degree opens many doors and supplies instant credibility. Each interview includes biographical notes and pictures. The book also includes a general introduction, a glossary, and appendixes describing the project's methodology.